2019
DOI: 10.21873/anticanres.13862
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Cytotoxicity Relationship of 2-Arylazolylchromones and 2-Triazolylchromones

Abstract: Background/Aim:4H-1-Benzopyran-4-one (chromone), present in various flavonoids as a backbone structure, has been used for the synthesis of anticancer drugs.The study aimed at investigating the cytotoxicity of eight 2arylazolylchromones and twelve 2-triazolylchromones against four human oral squamous cell carcinoma (OSCC) cell lines and three human normal mesenchymal oral cells, and then performed a quantitative structure-activity relationship (QSAR) analysis. Materials and Methods: Cell viability was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We investigated a total 291 compounds from 17 different groups ( A~Q ) of their cytotoxicity (assessed by CC 50 ) against four human OSCC (Ca9-22, HSC-2, HSC-3, and HSC-4) and three human normal mesenchymal cells (HGF, HPLF, and HPC), and then their tumor specificity (assessed by TS M , calculated as describe in Figure 2 , and potency-selectivity expression (PSE)) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. PSE, that reflects both tumor specificity and cytotoxicity against tumor cells, was calculated by dividing the TS M by CC 50 for tumor cells, and then multiplying by 100.…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated a total 291 compounds from 17 different groups ( A~Q ) of their cytotoxicity (assessed by CC 50 ) against four human OSCC (Ca9-22, HSC-2, HSC-3, and HSC-4) and three human normal mesenchymal cells (HGF, HPLF, and HPC), and then their tumor specificity (assessed by TS M , calculated as describe in Figure 2 , and potency-selectivity expression (PSE)) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. PSE, that reflects both tumor specificity and cytotoxicity against tumor cells, was calculated by dividing the TS M by CC 50 for tumor cells, and then multiplying by 100.…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
“…This demonstrated that only limited numbers of compounds show higher tumor specificity, although their structures are very similar with each other. It is possible that such highly tumor-specific compounds show the optimal 3D structure, since the tumor specificity of chromone compounds shows the tight correlation with chemical descriptors that reflect the 3-D structure ( Table 4 ) [ 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
“…The crystallographic structure of EGFR in complex with its ligand was obtained from the Protein Data Bank [11]. Molecular docking studies were performed with the Molecular Operating Environment 2019.0101 software (MOE of Chemical Computing Group Inc. (the license is issued to, revised, and renewed annually by Nahda University)) on Core i5 2.2 GHz workstation running on a Windows 10 PC [12]. Compoundsꞌ structures were built using ChemDraw Ultra 11.0, then their protonation, the correction of atoms and bond types were defined, hydrogen atoms were added, and finally minimization was performed (MMFF94x, gradient: 0.01) [13].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…al, having more than two aromatic rings leads to a higher tumor specificity. 9 The IC 50 values range from 36 µM (compound 6f) to 631 µM (compound 6j) for MCF-7 and 56 µM (compound 6f) to 558 µM (compound 6j) for A549 cells (Table 1). The most potent compound is compound 6f (Fig.…”
Section: The Cytotoxic Assaymentioning
confidence: 99%
“…Moreover, the chromone derivatives with a hydroxyl group in the 3-position in the pyrone ring are called 3-hydroxychromone. Chromone derivatives display a wide range of biological activities including antifungal, 3 antimicrobial, 4 antiobesity, 5 antiviral, 6,7 anti inflammatory, 8 anticancer, 9,10 antioxidant, 11 and protein kinase inhibitory. 12 In addition, chromones are good bidentate ligands able to coordinate metal ions.…”
Section: Introductionmentioning
confidence: 99%